The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1074/jbc.m112.374876
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 Is a Critical Transactivator for the Human IL1RL1/ST2 Promoter in Mast Cells/Basophils

Abstract: Background:The IL1RL1/ST2 gene encodes the receptor for IL-33, which is important for Th2 responses. Results: GATA2 knockdown reduced the expression of human IL1RL1/ST2 in KU812 and LAD2 cells and in human primary peripheral basophils. Conclusion: GATA2, but not GATA1, is a critical transcription factor for expression of human IL1RL1/ST2 in mast cell/ basophil lineages. Significance: GATA2 and GATA1 exhibit distinctive roles in the expression of human IL1RL1/ST2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 24 publications
0
44
0
7
Order By: Relevance
“…Although GATA1 was identified as a transactivator for the mouse MS4A2 (encoding FcεRIb) promoter (7,19), cell type-specific transcripThe Journal of Immunologytion factor that regulates human MS4A2 has not been identified to date. It has also been revealed that GATA2, which is also known to regulate mast cell development in a synergistic manner with PU.1 (20), is necessary for the promoter function of c-kit (18) and ST2/ IL1RL1 (IL-33R) (14) in mast cells. In the current study, we investigated the involvement of PU.1, GATA1, and GATA2 in the expression of FcεRI using a recently established highly effective knockdown of target mRNA in mast cells to verify our previous findings.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although GATA1 was identified as a transactivator for the mouse MS4A2 (encoding FcεRIb) promoter (7,19), cell type-specific transcripThe Journal of Immunologytion factor that regulates human MS4A2 has not been identified to date. It has also been revealed that GATA2, which is also known to regulate mast cell development in a synergistic manner with PU.1 (20), is necessary for the promoter function of c-kit (18) and ST2/ IL1RL1 (IL-33R) (14) in mast cells. In the current study, we investigated the involvement of PU.1, GATA1, and GATA2 in the expression of FcεRI using a recently established highly effective knockdown of target mRNA in mast cells to verify our previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, PU.1 and GATA1/GATA2 exhibit a cooperative function in mast cells, as follows: 1) PU.1 and GATA2 cooperatively induce mast cell development (20); 2) PU.1 and GATA1 synergistically transactivate cell type-specific gene regulation in mast cells (5,29); and 3) PU.1 is required for GATA1 expression in mast cells (30). In our previous studies, PU.1, GATA1, and GATA2 were identified as specific transcription factors that participate in the transcriptional regulation of certain genes expressed in mast cells, including human FCER1A (FcεRIa), mouse Ms4a2 (FcεRIb), mouse c-kit, and human ST2/ IL1RL1 (4,5,7,14,18,19). However, it has also been reported that knockdown of GATA1 and GATA2 by siRNA does not affect FcεRI expression in rodent mast cells and/or a basophilic cell line (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations